PENGEMBANGAN MODUL MENGGAMBAR PROPORSI TUBUH MATA KULIAH GAMBAR ANATOMI JURUSAN IKK FAKULTAS PARIWISATA DAN PERHOTELAN UNIVERSITAS NEGERI PADANG - Mawaddah, Khamilah; Ernawati, Ernawati; Nelmira, Weni (Journal of Home Economics and Tourism, 2017)
The purpose of the research as an effort to solve the college students problem in Gambar Anatomi lectures at drawing the proportions of the body, because students have difficulty in drawing body proportions. This research is a research and development known as Research and Development (R & D) which aims to produce a learning media valid and practical.The research procedures include define, design and develop stages. The data was from validity test, small group and big group of college students practicallity test, and advisor of Gambar Anatomi leature subject. The validity test given to 4 validator, practicallity test given to 10 college students, big group practicallity test given to 40 college students and given to 1 advisor of Textile Analysis lectures subject. Based validity test the researcher got score 4,54 which categorized as valid. The result of practicallity test from small group was got score 84,19% which categorized as very practical, big group test was got score 82,75% which categorized as very practical and test from advisor of lectures subject was got score 90,00% which categorized as very practical. So this module is proper to use as learning media.Keyword : Pengembangan Modul, Menggambar Proporsi Tubuh